PENERAPAN SISTEM DIGITALISASI BIO-REMEDIASI UNTUK PENGOLAHAN MIKROPLASTIK DAN PENYEDIAAN AIR BERSIH BERKELANJUTAN KEMANFAATANNYA TERHADAP MASYARAKAT DI PALANGKA RAYA - Abdurrahman, Abdurrahman; Munaji, Achmad Arif (EnviroScienteae, 2025)
Microplastic pollution has become a global issue, threatening water sources and human health. Palangka Raya, as a city with growing industrial and domestic activities, is increasingly vulnerable to contamination. Conventional water treatment methods are often ineffective in removing microplastics, while the demand for clean water continues to rise. Bioremediation offers an environmentally friendly solution by utilizing the ability of microorganisms to degrade pollutants, including microplastics.The aim of this study is to develop and implement a digitalized bioremediation system for microplastic treatment, supported by a digital platform in the form of a web-based system for data management and water quality monitoring in Palangka Raya. The specific objectives include: identifying microorganisms, designing and developing a Digital System (web-based) for data recording and management, and evaluating the effectiveness of the bioremediation process. This research employs a mixed-methods approach. The initial phase includes the isolation and characterization of microplastic-degrading microorganisms. A prototype bioremediation system is then developed and tested in the laboratory. The proposed Digital System will be designed as a web-based platform, where field personnel can manually input laboratory test results. Quantitative data will be analyzed statistically, while qualitative data will be collected through interviews to understand public perceptions and potential adoption.